Genetic differentiation of Anisakis species (Nematoda: Anisakidae) in marine fish Priacanthus tayenus from Gulf of Thailand - Eamsobhana, Praphathip; Yong, Hoi Sen; Song, Sze Looi; Tungtrongchitr, Anchalee; Roongruangchai, Kosol (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Members of the genus Anisakis are parasitic nematodes of the family Anisakidae. They are potential zoonotic parasites, causing anisakiasis in humans who consume raw or undercooked seafood (fish or squid) infected with the larvae of this nematode. In the present study, anisakid nematodes collected from the marine fish Priacanthus tayenus (Purple-spotted big-eye) caught from the Gulf of Thailand were examined morphologically and characterized genetically by DNA sequence analysis. Sequence data from the mitochondrial cytochrome c oxidase subunit II (mtDNA cox2) gene were used to identify these nematodes to species level and to evaluate the phylogenetic relationship among various taxa. All the 15 third-stage larvae of Anisakis nematodes investigated in this study belonged to the same genetic lineage as the A. typica species complex (named here as A. typica sp. T – T for Thailand). Eight mtDNA cox2 haplotypes were revealed in the 15 isolates of this Anisakis from Thailand. The mtDNA cox2 haplotypes of A. typica sp. T from Thailand were genetically distinct from those of the A. typica sensu stricto. Taxonomic description of this A. typica sp. T as a distinct species however awaits the availability of adult specimens.